Hubungan Mekanisme Koping dengan Kecemasan Pada Pasien Penyakit Ginjal Kronik Yang Menjalani Hemodialisa - Mailani, Fitri; Refnandes, Randy; Ranita, Nada Dwi (REAL in Nursing Journal, 2023)
Background: Patients with chronic kidney disease undergoing hemodialysis often experience anxiety. The response made by patients in facing anxiety can involve adaptive coping mechanisms or maladaptive coping mechanisms. The difference in these abilities affects the level of anxiety experienced by patients. The objective of this research is to determine the relationship between coping mechanisms and anxiety levels in patients with chronic kidney disease undergoing hemodialysis at Dr. M Djamil Padang General Hospital. Methods: The research method is quantitative with a cross-sectional study design. The analysis used is Spearman's correlation. The sample in the study consisted of 134 respondents using a purposive sampling technique. Data collection utilized the Brief COPE Questionnaire to assess coping mechanisms and the Zung Self Rating Anxiety Scale (ZSAS) Questionnaire to assess anxiety. Results: Based on the research results, the median value of coping mechanisms is 58.00, indicating maladaptive coping mechanisms, while the median value for anxiety is 62.00, indicating a moderate level of anxiety in patients. Bivariate analysis showed a significant relationship between coping mechanisms and anxiety in patients undergoing hemodialysis, with an average correlation strength and a negative direction (p-value = 0.000 and r = -0.506), meaning that the lower the coping mechanisms, the higher the anxiety experienced by hemodialysis patients. Conclusion: Promotive and preventive efforts are needed to address anxiety in patients undergoing hemodialysis. Healthcare professionals can contribute to this by conducting health education activities on anxiety management and coping mechanisms.Keywords: Anxiety, Coping Mechanisms, Hemodialysis